Aquatic plants of Pennsylvania : a complete reference guide - Block, Timothy A. (University of Pennsylvania Press, 2011)
The first complete identification guide to the aquatic plants of Pennsylvania, this reference provides illustrations and detailed descriptions of the more than 200 native and invasive species known to inhabit the Commonwealth's waterways.